2014
DOI: 10.1002/cphc.201301233
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of N2P2 Four‐Membered Rings

Abstract: The biradicaloid character of the ground‐state structures of N2P2 rings is studied by using the high‐level ab initio multiconfigurational CASPT2/CASSCF method. In order to obtain accurate descriptors, we combine two criteria: 1) singlet–triplet energy gaps and 2) relative values of the occupation numbers for bonding and antibonding orbitals associated with the radical sites. The singlet–triplet energy gaps, the occupation numbers of antibonding‐like orbitals, and the weights of the main configuration state fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…However, due to the presence of transition metals and the size of the system, we have optimized the complexes without symmetry constraints in their lowest singlet and triplet states at the B3LYP/6-311+G* level of theory. We have previously demonstrated that singlet–triplet energy gaps are accurately reproduced at this level of theory for unsubstituted P 2 N 2 H 2 rings . Herein we extend this study to substituted P 2 N 2 (CH 3 ) 2 rings 1 and 2 .…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…However, due to the presence of transition metals and the size of the system, we have optimized the complexes without symmetry constraints in their lowest singlet and triplet states at the B3LYP/6-311+G* level of theory. We have previously demonstrated that singlet–triplet energy gaps are accurately reproduced at this level of theory for unsubstituted P 2 N 2 H 2 rings . Herein we extend this study to substituted P 2 N 2 (CH 3 ) 2 rings 1 and 2 .…”
Section: Resultssupporting
confidence: 56%
“…In Figure S1 (see SI), the main geometrical parameters of the S 0 and T 1 structures are collected together with some energetic results. It should be mentioned that the biradicaloid character of compounds 1 and 2 has been previously studied using only the B3LYP singlet–triplet energy gaps . The S 0 optimized geometry of the N 2 P 2 core of compound 1 is almost identical to the experimental core obtained in the X-ray structure of biradicaloid [P(μ-NTer)] 2 in terms of planarity, distances, and angles.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…A peculiarity is presented by the species of type II , which were experimentally prepared by the group of Schulz and summarized in a recent reports . For the latter category interesting calculations appeared, the reader may be referred to this pertinent discussion . Since the aim of this review is a discussion of the Niecke‐type compounds further analysis on the homologues Ia and Ia(P) will not be given here.…”
Section: Discussionmentioning
confidence: 99%